Single-cell RNA sequencing reveals the role of immunoinflammatory cells in the progression of renal tubulointerstitial fibrosis - Xiaoqin Ye; Youcai Xu; Shanshan Wu; Yu Peng; Liwen Gao; Xi Huang; Lingfei Lu; Jiandong Lu; Xinhui Liu (PLoS ONE, 2025)
Renal tubulointerstitial fibrosis (TIF) is an independent risk factor for chronic kidney disease (CKD) progression and prognosis. It is known that immunoinflammatory cell infiltration plays a crucial role in TIF development and progression. However, what types of immunoinflammatory cells and by what means they promote TIF have not been fully clarified. In this study, mice models of unilateral ureteral obstruction (UUO) in which the left ureters were ligated for 3, 7, and 14 days, respectively, were used to simulate different levels of TIF severity. Single-cell RNA sequencing (scRNA-seq) was performed to characterize the immunoinflammatory cells in the kidneys of mice in each group. The results showed that the degree of renal pathological injury and expression level of fibrosis-related proteins increased over time in the UUO groups. Compared with the sham group, the proportion of T and NK cells, neutrophils, and mononuclear phagocyte cells was elevated in the kidney of UUO mice. Except for a decrease in the UUO7d group, the proportion of B cells did not differ notably between groups. The proportion of NaiveB_Ccl4 subset increased significantly in all UUO groups, and its up-regulated genes were mainly enriched in toll-like receptor signaling. The proportions of CD8Teff_Arhgap15, GDTCells_Trdc, HelperT_Tnf, and Treg_Foxp3 subsets were also significantly increased in all UUO groups, and their up-regulated genes were mainly enriched in NF-kappa B and TNF signaling. Neutrophils-4 subset was located at the terminal of neutrophil differentiation and mainly activated cytokine production and mitochondrial autophagy. Notably, the Macrophages_Arg1 subset had high scores in extracellular matrix remodeling, pro-angiogenesis, pro-inflammation, and immune regulation. Moreover, interactions between fibroblasts and immunoinflammatory cells increased with prolonged UUO time, with the strongest interactions with macrophages. When fibroblasts acted as ligand cells, the important interacting gene pairs with immunoinflammatory cells were CXCL6-CXCR1, APP-CD74, CX3CL1-CX3CR1, and THBS1-CD36, whereas when fibroblasts acted as receptor cells, the important interacting gene pairs with immunoinflammatory cells were TYROBP-CD44, TNF-TNFRSF1A, LGALS3-MERTK, PDGFA/B-PDGFRA, OSM-OSMR, and DKK2-LRP6. Overall, this study revealed the dynamic changes of immunoinflammatory cells and their interactions with fibroblasts in the kidneys during the UUO-induced TIF process.